Corporality in transformative education: A rescue for higher education - Barboza, Ricardo Barretto (Seven Editora, 2024)
Reflections on transformative education often encompass issues such as paradigm shifts, valuing the subject, affectivity in relationships, and more thought-provoking and effective ways of learning and teaching. Several authors and theories point to the body as an element to be recognized in these dynamics. However, the arguments about corporality, which designates the living and experiential character of the body, appear in general in a diffuse way throughout different works and discussions, and often quite focused on the education of children and adolescents. This article proposes to compile relevant arguments about the power of corporality in transformative education from the perspective of higher education, in order to contribute to the broadening and deepening of this path of research and reflection. To this end, it conducts a literature review that identifies the issue of corporality in transformative education in terms of paradigms, subjectivity, organicity and pedagogy. DOI:https://doi.org/10.56238/sevened2024.007-096